Integrated Tourism Development: an Institutional Management Priority Study - Fajrin Hardinandar; Gufran Gufran (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2022)
At least 200 people per day visit the hilly area of Matakando which has the potential for culinary tourism, rice fields, and education that are very likely to be developed. The purpose of this study is to find a management pattern for the development of tourism centers that can integrate the three types of tourism. The criteria and alternative indicators were obtained from the Focus Group Discussion (FGD) held in August 2022. Using the Analytical Hierarchy Process (AHP) method, we confirmed that culinary tourism is a priority, which will be developed into integrated rice field tourism and education. Alternative development strategies that need to be carried out are rearranging the structure and management of tourism, training in the management of tourism institutions, increasing creativity for business actors, developing infrastructure, increasing marketing capabilities, compiling strategic plan documents, and enforcing green zones.